Cho F(x) = (x – 1)e^x là một nguyên hàm của hàm số f(x)e^2x. Tìm nguyên hàm

Câu hỏi :

Cho F(x) = (x – 1)ex  là một nguyên hàm của hàm số f(x)e2x. Tìm nguyên hàm của hàm số f '(x)e2x

* Đáp án

* Hướng dẫn giải

Do F(x) = (x – 1)ex là một nguyên hàm của f(x)e2x nên:

F '(x) = f(x)e2x

Û xex = f(x)e2x

Û f(x) = xex.

Suy ra : f '(x) = exxexex2=1xexe2x 

Þ f '(x) = (1 – x)ex.

Khi đó f'(x)e2xdx=(1x)exdx 

Đặt u=1xdv=exdxdu=dxv=ex

Do đó: f'(x)e2xdx = (1 – x)ex + exdx 

= (1 – x)ex + ex = (2 – x)ex + C.

Copyright © 2021 HOCTAP247